The Tower Room - Geras, Adele (Harcourt Brace Jovanovich, Publisher, 1990)
In a scene that echoes Rapunzel, Megan looks down from her tower room at a cloistered all-girls boarding school in England and observes the arrival of the new laboratory assistant, Simon Findlay. As soon as their eyes meet, their love blossoms--and Simon begins to scale the scaffolding into the tower room for clandestine trysts. But when Dorothy, the school's science teacher and Megan's guardian, discovers the young couple's affair, Megan's sheltered world is shattered forever.
Keywords: Juvenile Fiction; Love & Romance